Intranasal infection by SARS-CoV-2 Omicron variants can induce inflammatory brain damage in newly weaned hamsters - Can Li; Wenchen Song; Jasper Fuk-Woo Chan; Yanxia Chen; Feifei Liu; Zhanhong Ye; Alvin Hiu-Chung Lam; Jianpiao Cai; Andrew Chak-Yiu Lee; Bosco Ho-Yin Wong; Hin Chu; David Christopher Lung; et al. (Emerging Microbes and Infections)
Children infected by SARS-CoV-2 Omicron variant may develop neurological complications. To study the pathogenesis in the growing brain, we intranasally challenged newly-weaned or mature hamsters with SARS-CoV-2 Omicron BA.2, BA.5, or Delta variant. Omicron BA.2 and Delta infection produced a significantly lower viral load in the lung tissues of newly-weaned than mature hamsters despite comparable histopathological damages. Newly-weaned hamsters had higher brain viral load, significantly increased cerebrospinal fluid concentration of TNF-α and CXCL10 and inflammatory damages including mild meningitis and parenchymal vascular congestion, despite sparse expression of nucleocapsid antigen in brain cells. Furthermore, 63.6% (28/44) of all SARS-CoV-2 infected newly-weaned hamsters showed microgliosis in olfactory bulb (OB), cerebral cortex, and hippocampus. In infected mature hamsters, microgliosis was observed mainly in OB and olfactory cortex of 35.3% (12/34) of their brains. Neuronal degeneration was found in 75% (33/44) of newly-weaned hamsters affecting multiple regions including OB, olfactory cortex, midbrain cortex, and hippocampus, while such changes were mainly observed in the hippocampus of mature hamsters. Importantly, similar brain histopathology was also observed in Omicron BA.5-infected newly-weaned hamsters. Our study suggested that SARS-CoV-2 may affect the brain at a young age. This kind of brain involvement and histological changes are not virus variant or subvariant specific. Incidentally, a moderate amount of eosinophilic infiltration was observed in the mucosa of nasal turbinate and trachea of newly-weaned hamsters infected by Omicron BA.2 and BA.5 but not Delta variant. This histological finding is consistent with the higher incidence of laryngotracheobronchitis in young children infected by the Omicron variant.Summary Intranasal infection of newly-weaned Syrian hamsters by SARS-CoV-2 Omicron variants can lead to brain inflammation and neuron degeneration with detectable low level of viral load and sparse expression of viral nucleoprotein.